Tissue factor signal transduction in angiogenesis - Versteeg, Henri H.; Peppelenbosch, Maikel P.; Spek, C. Arnold (Carcinogenesis (New York), 2003)
Tissue factor (TF), a 47-kDa transmembrane glycoprotein, is a principal regulator of oncogenic neoangiogenesis and controls therefore the cancerous process. Although originally identified as a component of the coagulation cascade, it has become clear that TF functions as a cytokine-like receptor and this notion was confirmed by the discovery of coagulation-independent actions of TF (which include regulation of tumour growth, embryonic and oncogenic blood vessel formation as well as regulation of inflammation and sepsis). In accordance, TF-mediated signal transduction events are readily detected and the elucidation of the underlying molecular mechanisms has recently seen spectacular progress and it is now understood that the role of TF in angiogenesis is both coagulation-dependent and independent. The recent evidence for this emerging insight will be the subject of this review.